Tin-doped layered manganese oxide electrocatalytic material, preparation method thereof and hydrogen fuel cell electrocatalyst
By doping tin elements into layered lithium manganate, tin-doped layered manganese oxide electrocatalytic material was prepared, which solved the problems of insufficient catalytic activity and poor structural stability in the oxygen reduction reaction of existing manganese oxide catalysts. The effect of significantly improving the catalytic performance and structural stability of the oxygen reduction reaction is achieved.
Patent Information
- Application Number
- CN202310941551.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
AI Technical Summary
The existing manganese oxide catalysts have problems such as insufficient catalytic activity, large overpotential and poor structural stability in oxygen reduction reactions, making it difficult to react completely according to the direct four-electron pathway, and during the long-term cycle, the material will be active due to the dissolution of manganese ions. loss.
By doping tin elements into layered O3 lithium manganate, a tin-doped layered manganese oxide electrocatalytic material is prepared, with the chemical formula of Li2Mn1-xSnxO3, 0
The tin-doped layered manganese oxide electrocatalytic material significantly improves the catalytic performance of the oxygen reduction reaction, reduces the overpotential, and enhances the structural stability of the material, so as to maintain high oxygen reduction activity under alkaline conditions .
Smart Images

Figure CN119430292A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of inorganic materials, and in particular relates to a tin-doped layered manganese oxide electrocatalytic material, a preparation method thereof, and a hydrogen fuel cell electrocatalyst. Background Art
[0002] With the increasing demand for efficient, clean new energy and sustainable energy conversion technologies, getting rid of dependence on traditional fossil fuels and realizing the transformation and optimization of energy methods will become an inevitable development trend. Fuel cells are considered to be a green power generation method with broad prospects due to their many advantages such as not being restricted by the Carnot cycle, high energy conversion efficiency, and no pollution to the environment. Taking hydrogen and oxygen fuel cells as an example, the anode side undergoes a hydrogen oxidation reaction under the action of a catalyst, and electrons flow from the anode to the cathode through an external circuit. Oxygen reduction reaction occurs on the cathode side under the action of the cathode catalyst. Among them, the oxygen reduction reaction is considered to be the main bottleneck limiting the overall reaction efficiency due to its slow kinetics, large overpotential and complex intermediate processes. Therefore, the development of efficient and stable oxygen reduction catalysts is of great significance to the widespread application and commercialization of fuel cells.
[0003] At present, platinum group noble metals are still the preferred catalysts for oxygen reduction reactions, but the high cost of fuel cells due to the scarcity of platinum group metals. Therefore, the development of low-cost, non-precious metal catalysts with good oxygen reduction catalytic activity and long-term stability to replace platinum group catalysts is the main research direction for the development of oxygen reduction electrocatalysts. In recent years, researchers have developed a variety of non-precious metal oxygen reduction catalysts to overcome the cost problem of fuel cell catalysts. Among them, manganese oxides have attracted much attention due to their low price and environmental friendliness. However, existing studies have shown that compared with precious metal catalysts, manganese oxide catalysts usually cannot make the oxygen reduction reaction proceed completely according to the direct four-electron pathway, and have a large overpotential. In addition, during long-term cycles, the material will lose activity due to the dissolution of manganese ions. Therefore, improving the activity and stability of the catalyst through a simple method is the focus of developing non-precious metal oxidant catalysts with excellent performance. Summary of the invention
[0004] The present invention is made to solve the above problems, and aims to provide a tin-doped layered manganese oxide electrocatalytic material, a preparation method thereof, and a hydrogen fuel cell electrocatalyst.
[0005] The present invention provides a tin-doped layered manganese oxide electrocatalytic material having the following characteristics and a chemical formula: Li2Mn 1-x Sn x O3, where 0 <x<0.15。
[0006] The tin-doped layered manganese oxide electrocatalytic material provided by the present invention may also have the following characteristics: wherein 0.05≤x≤0.10.
[0007] The tin-doped layered manganese oxide electrocatalytic material provided by the present invention may also have the following characteristics: wherein x=0.1.
[0008] The present invention also provides a tin-doped layered manganese oxide electrocatalytic material having the following characteristics, comprising the following steps: step 1, weighing appropriate amounts of lithium hydroxide, manganese carbonate and stannous oxalate and preliminarily mixing them in an agate mortar to obtain a mixed powder; step 2, placing the mixed powder solution in a high-energy ball mill for grinding to obtain a ground sample; step 3, placing the ground sample in a muffle furnace for reaction at 400°C-500°C for 36h-48h to obtain a tin-doped layered manganese oxide electrocatalytic material, wherein in step 1, the molar ratio of lithium hydroxide, manganese carbonate and stannous oxalate is 2.05:(1-x):x.
[0009] The method for preparing the tin-doped layered manganese oxide electrocatalytic material provided by the present invention may also have the following feature: wherein, in step 2, grinding is performed at a rate of 400 rpm-500 rpm for 6 hours.
[0010] The method for preparing the tin-doped layered manganese oxide electrocatalytic material provided by the present invention may also have the following feature: wherein, in step 3, the gas used for the reaction in the muffle furnace is air.
[0011] The method for preparing the tin-doped layered manganese oxide electrocatalytic material provided by the present invention may also have the following characteristics: wherein, in step 3, the temperature is increased to 400° C.-500° C. at a heating rate of 5° C. / min in a muffle furnace.
[0012] The present invention also provides a hydrogen fuel cell electrocatalyst comprising the tin-doped layered manganese oxide electrocatalytic material.
[0013] The hydrogen fuel cell electrocatalyst provided by the present invention may also have the following characteristics, and further include: carbon powder, and the mass ratio of the tin-doped layered manganese oxide electrocatalytic material to the carbon powder is 1:9 to 3:7.
[0014] The hydrogen fuel cell electrocatalyst provided by the present invention may also have the following characteristics: wherein the hydrogen fuel cell electrocatalyst is made by mixing and grinding a tin-doped layered manganese oxide electrocatalytic material and carbon powder, and the model of the carbon powder is VulcanXC-72R.
[0015] Functions and Effects of the Invention
[0016] According to the tin-doped layered manganese oxide electrocatalytic material and hydrogen fuel cell electrocatalyst involved in the present invention, since the chemical formula of the tin-doped layered manganese oxide electrocatalytic material is Li2Mn 1-x Sn x O3, where 0 < x < 0.15. On the one hand, this electrocatalytic material does not contain platinum group metals and has a cost advantage; on the other hand, by doping tin elements into layered O3-type lithium manganate (Li2MnO3), the catalytic performance of its electrocatalytic oxygen reduction reaction is significantly improved under the synergistic effect of tin elements, and at the same time, the structural stability of the material is enhanced.
[0017] According to the preparation method of the tin-doped layered manganese oxide electrocatalytic material involved in the present invention, since the well-established layered lithium manganate (Li2MnO3) is selected as the precursor and prepared by simple mechanical ball milling and calcination processes, the present invention has the advantages of simple preparation method and easy scale-up; in addition, since an electrocatalytic material with high oxygen reduction activity can be prepared by doping inexpensive precursor stannous oxalate into the well-established layered lithium manganate (Li2MnO3), the present invention has the advantages of low cost.
[0018] In addition, the tin-doped layered manganese oxide electrocatalytic material prepared according to the preparation method involved in the present invention has a large specific surface area, which can provide a larger active surface area and more active sites for the contact between the electrolyte and the catalyst, and can effectively improve the oxygen reduction performance of the catalyst.
[0019] In addition, for the tin-doped layered manganese oxide electrocatalytic material prepared according to the preparation method involved in the present invention, since there is a synergistic effect between tin atoms and manganese atoms in the material structure, the electronic structure can be effectively adjusted, the intermediate steps of the oxygen reduction reaction can be promoted, and the catalytic activity and structural stability of the material can be improved. The design of this structure enables the manganese oxide electrocatalytic material to have high oxygen reduction activity under alkaline conditions and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a schematic structural diagram of the layered lithium manganate (Li2MnO3) precursor in Comparative Example 1 of the present invention;
[0021] Figure 2 is a schematic structural diagram of Li2Mn 0.95 Sn 0.05 O3 in Example 2 of the present invention;
[0022] Figure 3 is a schematic structural diagram of the tin-doped layered manganese oxide electrocatalytic material and hydrogen fuel cell electrocatalyst (Li2Mn 0.9 Sn 0.1 O3) in Example 1 of the present invention;
[0023] Figure 4 The present invention is a tin-doped layered manganese oxide electrocatalytic material and a hydrogen fuel cell electrocatalyst (Li2Mn 0.9 Sn 0.1 O3), Comparative Example 1 (Li2MnO3), Example 2 (Li2Mn 0.95 Sn 0.05 O3), Example 3 (Li2Mn 0.85 Sn 0.15 O3) X-ray diffractometer experimental spectrum;
[0024] Figure 5 It is the X-ray diffractometer diagram and simulated spectrum of comparative example 2 (Li2SnO3);
[0025] Figure 6 The tin-doped layered manganese oxide electrocatalyst material (Li2Mn 0.9 Sn 0.1 O3), Comparative Example 1 (Li2MnO3), Example 2 (Li2Mn 0.95 Sn 0.05 O3), oxygen reduction polarization curves of hydrogen fuel cell electrocatalysts prepared in Comparative Example 2 (Li2SnO3);
[0026] Figure 7 The tin-doped layered manganese oxide electrocatalyst material (Li2Mn 0.9 Sn 0.1 O3), Comparative Example 1 (Li2MnO3), Example 2 (Li2Mn 0.95 Sn 0.05 O3), the number of electron transfers of the hydrogen fuel cell electrocatalyst prepared in Comparative Example 2 (Li2SnO3);
[0027] Figure 8 The tin-doped layered manganese oxide electrocatalyst material (Li2Mn 0.9 Sn 0.1 The stability diagram of the catalyst prepared by O3 after 10000 cycles of cyclic voltammetry at a scan rate of 100 mV / s;
[0028] Fig. 9 Example 1 (Li2Mn 0.9 Sn 0.1 O3), Comparative Example 1 (Li2MnO3), Example 2 (Li2Mn 0.95 Sn 0.05 O3) materials are assembled into alkaline fuel cell performance diagram. DETAILED DESCRIPTION
[0029] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following is a detailed description of a tin-doped layered manganese oxide electrocatalytic material, a preparation method thereof and a hydrogen fuel cell electrocatalyst of the present invention in combination with embodiments and drawings.
[0030] <Example 1>
[0031] This embodiment provides a tin-doped layered manganese oxide electrocatalytic material, and the preparation method thereof comprises the following steps:
[0032] Step 1: Grind 0.525 g of anhydrous lithium hydroxide, 1.08 g of manganese carbonate and 0.216 g of stannous oxalate in an agate mortar to obtain a mixed powder.
[0033] Step 2: Place the mixed powder in a high-energy ball mill and mill at a rate of 400 rpm for 6 hours to obtain a ground sample.
[0034] Step 3: Place the ground sample in a muffle furnace, heat it to 450°C at a heating rate of 5°C / min, and react for 40 hours to obtain a powder, namely, a tin-doped layered manganese oxide electrocatalyst material (Li2Mn 0.9 Sn 0.1 O3), whose structure is Figure 3 As shown in the figure, the X-ray diffractometer experimental spectrum is as follows Figure 4 shown.
[0035] <Example 2>
[0036] This embodiment 2 provides a Li2Mn 0.95 Sn 0.05 O3, the preparation method thereof comprises the following steps:
[0037] Step 1: Grind 0.525 g of anhydrous lithium hydroxide, 1.14 g of manganese carbonate and 0.108 g of stannous oxalate in an agate mortar to obtain a mixed powder.
[0038] Step 2: Place the uniformly mixed powder in a high-energy ball mill and ball mill it at a rate of 400 rpm for 6 h to obtain a ground sample.
[0039] Step 3: Place the ground sample in a muffle furnace and heat it to 450°C at a heating rate of 5°C / min. After reacting for 40 hours, a powder is obtained, namely Li2Mn 0.95 Sn 0.05 O3, whose structure is Figure 2 As shown in the figure, the X-ray diffractometer experimental spectrum is as follows Figure 4 shown.
[0040] <Example 3>
[0041] This embodiment 3 provides a Li2Mn 0.85 Sn 0.15 O3, the preparation method comprises the following steps:
[0042] Step 1: Grind 0.525 g of anhydrous lithium hydroxide, 1.02 g of manganese carbonate and 0.324 g of stannous oxalate in an agate mortar to obtain a mixed powder.
[0043] Step 2: Place the uniformly mixed powder in a high-energy ball mill and ball mill it at a rate of 400 rpm for 6 h to obtain a ground sample.
[0044] Step 3: Place the ground sample in a muffle furnace and heat it to 450°C at a heating rate of 5°C / min. After reacting for 40 hours, a powder is obtained, namely Li2Mn 0.85 Sn 0.15 O3.
[0045] Li2Mn 0.85 Sn 0.15 The X-ray diffractometer experimental spectrum of O3 is as follows Figure 4 As shown, through Figure 4 The data analysis proved the existence of a second phase in its structure.
[0046] <Comparative Example 1>
[0047] Comparative Example 1 provides an O3-type layered lithium manganese oxide, and the preparation method is as follows:
[0048] 0.315g of anhydrous lithium hydroxide and 0.720g of manganese carbonate were placed in an agate mortar for grinding. After mixing evenly, they were placed in a high-energy ball mill and ball-milled at a rate of 400rpm for 6h. After the ball milling was completed, the obtained powder was placed in a muffle furnace and reacted at 450°C for 40h to obtain a powder, which was O3-type layered lithium manganate (Li2MnO3).
[0049] <Comparative Example 2>
[0050] Comparative Example 2 provides a Li2SnO3, and the preparation method is as follows:
[0051] 0.525g lithium carbonate and 1.399g stannous oxalate were ground in an agate mortar. After mixing evenly, they were placed in a high-energy ball mill and ball-milled at 400rpm for 6h. After the ball milling, the obtained powder was pressed into sheets with a dry pressing mold, placed in a muffle furnace, reacted at 800℃ for 6h, then at 900℃ for 12h, and then at 1100℃ for 12h. Between different reaction temperatures, the pressed powder needs to be re-grinded and pressed into sheets with a dry pressing mold again for the next sintering. The final powder is Li2SnO3.
[0052] <Test Example 1>
[0053] X-ray diffraction.
[0054] X-ray diffraction was performed on the compounds obtained in Examples 1-3 and Comparative Examples 1-2. The characterization results are as follows: Figure 4-5 shown.
[0055] Figure 4 The present invention implements 1 (Li2Mn 0.9 Sn 0.1 O3) and Comparative Example 1 (Li2MnO3), Example 2 (Li2Mn 0.95 Sn 0.05 O3), Example 3 (Li2Mn 0.85 Sn 0.15 O3) X-ray diffractometer experimental spectrum.
[0056] like Figure 4 As shown, Example 3 (Li2Mn 0.85 Sn 0.15 O3) has a second phase, and the electrochemical performance will not be discussed further.
[0057] Figure 5 It is the X-ray diffractometer diagram (XRD) and simulation spectrum of comparative example 2 (Li2SnO3) of the present invention.
[0058] like Figure 5 As shown, the structure of Comparative Example 2 (Li2SnO3) was refined by the Rietveld method (Rietveld, 1969). The experimental spectrum after structural refinement is in good agreement with the calculated spectrum.
[0059] <Test Example 2>
[0060] Catalytic performance test of materials
[0061] The tin-doped layered manganese oxide electrocatalyst material (Li2Mn 0.9 Sn 0.1 O3) add carbon powder (mass ratio of 30%:70%, carbon powder model is Vulcan XC-72R) and grind in an agate mortar for 0.5 hours to obtain a hydrogen fuel cell electrocatalyst. The hydrogen fuel cell electrocatalyst is placed in a glass bottle, 1900 microliters of ethanol is added, and ultrasonic mixing is carried out in an ultrasonic machine for 2 hours. In the obtained mixed solution, 50 microliters of Nafion (5wt.%) are added and ultrasonic mixing is continued for 1 hour. Take an appropriate amount of the uniformly mixed solution obtained above and apply it on the surface of the glassy carbon electrode. The rotary drying method is used to obtain a uniformly covered catalyst film to control the Li2Mn 0.9 Sn 0.1 The O3 loading is 0.311 mg / cm2 The catalytic performance of the material was characterized by an electrochemical workstation.
[0062] Take the O3-type layered lithium manganese oxide (Li2MnO3) prepared in Comparative Example 1, add carbon black (mass ratio of 30%:70%), place it in an agate mortar and grind it for 0.5 hours, place it in a glass bottle, add 1900 microliters of ethanol, and then ultrasonically mix it in an ultrasonic machine for 2 hours. In the obtained mixed solution, add 50 microliters of Nafion (5wt.%) and continue ultrasonic mixing for 1 hour. Take an appropriate amount of the uniformly mixed solution obtained above and drop it on the surface of the glassy carbon electrode, and use the rotary drying method to obtain a uniformly covered catalyst film, and control the Li2MnO3 loading to 0.311mg / cm 2 The catalytic performance of the material was characterized by an electrochemical workstation.
[0063] Take the Li2Mn prepared in Example 2 0.95 Sn 0.05 O3 was added with carbon black (mass ratio of 30%:70%) and ground in an agate mortar for 0.5 hours. Then, it was placed in a glass bottle, 1900 microliters of ethanol was added, and ultrasonic mixing was performed in an ultrasonic machine for 2 hours. In the obtained mixed solution, 50 microliters of Nafion (5wt.%) was added and ultrasonic mixing was continued for 1 hour. An appropriate amount of the uniformly mixed solution obtained above was dropped and applied on the surface of the glassy carbon electrode. A uniformly covered catalyst film was obtained by rotary drying to control the Li2Mn 0.95 Sn 0.05 The O3 loading is 0.311 mg / cm 2 The catalytic performance of the material was characterized by an electrochemical workstation.
[0064] Take the Li2SnO3 prepared in Comparative Example 2, add carbon black (mass ratio of 30%:70%), grind in an agate mortar for 0.5 hours, put in a glass bottle, add 1900 microliters of ethanol, and then ultrasonically mix in an ultrasonic machine for 2 hours. Add 50 microliters of Nafion (5wt.%) to the obtained mixed solution and continue ultrasonic mixing for 1 hour. Take an appropriate amount of the uniform mixed solution obtained above and drop it on the surface of the glassy carbon electrode, and use the rotary drying method to obtain a uniformly covered catalyst film, and control the Li2SnO3 loading to 0.311 mg / cm 2 The catalytic performance of the material was characterized by an electrochemical workstation.
[0065] The model of carbon black used in this test example is VulcanXC-72R.
[0066] Test results such as Figure 6-8 shown.
[0067] Figure 6 The tin-doped layered manganese oxide electrocatalyst material (Li2Mn 0.9 Sn0.1 O3), Comparative Example 1 (Li2MnO3), Example 2 (Li2Mn 0.95 Sn 0.05 Oxygen reduction polarization curves of hydrogen fuel cell electrocatalysts prepared by Example 2 (Li2SnO3) and Comparative Example 2 (Li2SnO3).
[0068] like Figure 6 As shown, tin-doped layered manganese oxide electrocatalytic materials and hydrogen fuel cell electrocatalysts (Li2Mn 0.9 Sn 0.1 O3) has the largest limiting diffusion current and the smallest overpotential, and has the best oxygen reduction performance.
[0069] Figure 7 The tin-doped layered manganese oxide electrocatalyst material (Li2Mn 0.9 Sn 0.1 O3), Comparative Example 1 (Li2MnO3), Example 2 (Li2Mn 0.95 Sn 0.05 O3) and the number of electron transfer of the hydrogen fuel cell electrocatalyst prepared in Comparative Example 2 (Li2SnO3).
[0070] like Figure 7 As shown, in the voltage range of 0.4-0.8V vs.RHE, for tin-doped layered manganese oxide electrocatalysts and hydrogen fuel cell electrocatalysts (Li2Mn 0.9 Sn 0.1 O3), the electron transfer number is above 3.5.
[0071] Figure 8 The tin-doped layered manganese oxide electrocatalyst material (Li2Mn 0.9 Sn 0.1 Stability diagram of the catalyst prepared by O3) after 10000 cycles of cyclic voltammetry at a scan rate of 100mV / s.
[0072] like Figure 8 As shown, tin-doped layered manganese oxide electrocatalytic materials and hydrogen fuel cell electrocatalysts (Li2Mn 0.9 Sn 0.1 O3) exhibits excellent cycling stability.
[0073] <Test Example 3>
[0074] Alkaline fuel cell performance test
[0075] Using the tin-doped layered manganese oxide electrocatalytic material and hydrogen fuel cell electrocatalyst (Li2Mn 0.9 Sn 0.1O3) was assembled into an alkaline fuel cell. In the test, an alkaline polymer electrolyte (quaternaryammonia poly(N-methyl-piperidine-co-p-terphenyl), QAPPT) was used as the electrolyte membrane. PtRu / C was used as the anode catalyst, and the metal loading was controlled at 0.4 mg / cm 2 Example 1 (Li2Mn 0.9 Sn 0.1 O3), Comparative Example 1 (Li2MnO3), Example 2 (Li2Mn 0.95 Sn 0.05 O3) as the cathode catalyst, mixed with XC-72 at a mass ratio of 2:3, and the oxide loading was controlled to be 0.6 mg / cm 2 The test was conducted using the 850e MultiRange fuel cell test system at a temperature of 80°C and a pressure of 0.2Mpa. Fig. 9 shown.
[0076] Fig. 9 Example 1 (Li2Mn 0.9 Sn 0.1 O3), Comparative Example 1 (Li2MnO3), Example 2 (Li2Mn 0.95 Sn 0.05 O3) materials are assembled into alkaline fuel cell performance diagram.
[0077] like Fig. 9 As shown, the alkaline fuel cell assembled in Example 1 has excellent performance. The tin-doped layered manganese oxide electrocatalyst material (Li2Mn 0.9 Sn 0.1 O3) and hydrogen fuel cell electrocatalysts, because of the synergistic effect between tin atoms and manganese atoms in the material structure, it can effectively adjust the electronic structure, promote the intermediate steps of the oxygen reduction reaction, and improve the oxygen reduction performance.
[0078] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.
Claims
1. A tin-doped layered manganese oxide electrocatalytic material, characterized in that: The chemical formula is as follows: Li2Mn 1-x Sn x O3, where 0 <x<0.15。 2. The tin-doped layered manganese oxide electrocatalytic material according to claim 1, characterized in that: in, 0.05≤x≤0.10。 3. The tin-doped layered manganese oxide electrocatalytic material according to claim 1, characterized in that: in, x=0.1。 4. A method for preparing a tin-doped layered manganese oxide electrocatalytic material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, weighing appropriate amounts of lithium hydroxide, manganese carbonate and stannous oxalate and preliminarily mixing them in an agate mortar to obtain a mixed powder; Step 2, grinding the mixed powder in a high-energy ball mill to obtain a ground sample; Step 3, placing the ground sample in a muffle furnace and reacting at 400° C.-500° C. for 36 h-48 h to obtain the tin-doped layered manganese oxide electrocatalytic material, Wherein, in step 1, the molar ratio of the lithium hydroxide, the manganese carbonate and the stannous oxalate is 2.05:(1-x):x.
5. The method for preparing the tin-doped layered manganese oxide electrocatalytic material according to claim 1, characterized in that: in, In step 2, grinding was performed at a rate of 400-500 rpm for 6 h.
6. The method for preparing the tin-doped layered manganese oxide electrocatalytic material according to claim 1, characterized in that: in, In step 3, the gas used for the reaction in the muffle furnace is air.
7. The method for preparing the tin-doped layered manganese oxide electrocatalytic material according to claim 1, characterized in that: in, In step 3, the temperature is increased to 400° C.-500° C. at a heating rate of 5° C. / min in a muffle furnace.
8. A hydrogen fuel cell electrocatalyst, characterized in that include: The tin-doped layered manganese oxide electrocatalytic material according to any one of claims 1 to 3.
9. The hydrogen fuel cell electrocatalyst according to claim 8, characterized in that: Also includes: Carbon powder, the mass ratio of the tin-doped layered manganese oxide electrocatalytic material to the carbon powder is 1:9 to 3:
7.
10. The hydrogen fuel cell electrocatalyst according to claim 9, characterized in that: in, The hydrogen fuel cell electrocatalyst is prepared by mixing and grinding the tin-doped layered manganese oxide electrocatalytic material and the carbon powder. The model of the carbon powder is Vulcan XC-72R.